Penerapan Pembelajaran Cooperative Learning Tipe Make A Match Dalam Menstimulasi Logic Matematika Anak Usia Dini - Agus Sriyanto; Maragustam Siregar; Siti Fatonah (UIN Sultan Maulana Hasanudin Banten, 2023)
The application of make a match cooperative learning paradigm to stimulate early childhood math logic is the main discussion in this research. The purpose of this study was to determine the application of make a match cooperative learning in stimulating early childhood math logic. The research method used is descriptive qualitative with sampling using purpossive technique. The results showed: 1) The learning atmosphere of math introduction through cooperative learning model runs well. 2) In addition to gaining basic math knowledge, children's social skills also improved. Children are able to learn and cooperate with the group. 3) Logical intelligence that can be improved includes; Logical reasoning and mathematical reasoning, number sense and problem solving, 4) Some supporting factors in learning mathematics for early childhood are; 1) Cognitive development, 2) Experience and learning environment, 3) Motivation and interest of children, 4) Practice opportunities.